Chromatin recruitment of DNA repair proteins: lessons from the fanconi anemia and double-strand break repair pathways. - Cohn, M; D'Andrea, A (2008)
In response to DNA damage, eukaryotic cells must rapidly load DNA repair proteins onto damaged chromatin. Chromatin recruitment often entails ubiquitination of a damage-specific DNA repair protein, interaction with a ubiquitin binding factor, assembly of a multisubunit DNA repair complex, and eventually a deubiquitination event once the DNA repair reaction has been completed. This review focuses on the recent discoveries in the Fanconi Anemia (FA) and DNA double-strand break (DSB) repair pathways, which underscore the importance of regulated chromatin loading in the DNA damage response. Interestingly, these two pathways share several features, suggesting a more general mechanism for DNA-repair regulation.